상품에서 자산으로: 권력으로서의 자본과 금융의 존재론; From Commodities to Assets: Capital as Power and the Ontology of Finance - Jesús Suaste Cherizola (Akaroot, 2023)
자산은 자본가 계급의 실천 및 사고방식을 형성하는 데 결정적인 개념이다. 하지만 자본 주의에 관한 비판적 분석은 상품교환을 자본주의 분석의 초석이라 승인하는 경향이 있다. 이 논문은 다른 접근법을 취한다. 나는 자산이 자본주의에 대한 과학적 연구를 위한 견고한 출발점을 제공한다고 주장한다. 자산에 대한 분석은 경제적 거래에 대한 일반적 서술을 정 교화할 수 있도록 해주고, 그런 한에서, 자산 분석은 금융 분야를 재개념화하기 위한 기틀 을 마련해줄 수 있다. 이 두 가지 쟁점은 밀접히 연관된다. `자산이란 무엇인가'라는 질 문에 대한 답은 `금융이란 무엇인가'라는 질문을 해결할 수 있는 좌표를 제공해줄 것이 다. 저자 제수스 수아스테 체리졸라(JesÚs Suaste Cherizola)는 멕시코 푸에블라 오토노마 대학교(Universidad Autónoma de Puebla)에서 박사학위를 받았고, 권력자본 이론을 전공하는 사회학자이다. 저자는 이 논문을 통해 경제학과 사회과학에 새로운 아이디어를 제공한 기여로 2021 CASP Essay Prize를 수상했다. 따라서 제도주의 경제학 현장에서 이 논문이 지니는 학술적 가치가 높은 평가를 받았다고 볼 수 있다. – – Translated by Yong-taek Jung (Korean): In this paper, the author analyzes the concept of 'assets', a crucial concept in the practice and mindset of today's capitalist class. In particular, it emphasizes the emerging importance of assets in financialized capitalism by contrasting them with the concept of commodities, which have enjoyed an important place in the analysis of conventional capitalism. Recently, in the critical academia of finance and money in the West, especially in the sociology of finance, the concepts of capitalization and assetization are emerging as a powerful analytical framework that reveals the characteristics of modern capitalism by replacing the existing commercialization and financialization. The paper provides a clear explanation of the concept of asset, capitalization, and capitalization from the perspective of power capital theory. In addition, by emphasizing the difference between commodity exchange and asset trading, which has been presented centering on the existing Marxism, it explains well why the asset type and the process of assetization can be an important analytical framework for studying today's financial capitalism. Therefore, this paper in domestic academia, it can provide impetus to advance the discussion of financialization in terms of capitalization and assetization, and it can also serve as a useful reference point for understanding recent academic discussions on the changes and core of modern capitalism. Author Jesús Suaste Cherizola is a sociologist who received her Ph.D. from Universidad Autónoma de Puebla, Mexico, and specializes in power capital theory. The author won the 2021 CASP Essay Prize for his contributions to new ideas in economics and social sciences with this paper. Therefore, it can be said that the academic value of this thesis has been highly evaluated in the field of institutional economics.
Keywords: P; P1; P14; P46; G12; G3; 330; assets; commodities; finance; financialization; ownership; power; property; value